2021
DOI: 10.15252/embr.202051606
|View full text |Cite
|
Sign up to set email alerts
|

OXPHOS deficiency activates global adaptation pathways to maintain mitochondrial membrane potential

Abstract: Reduction of mitochondrial membrane potential (Δψm) is a hallmark of mitochondrial dysfunction. It activates adaptive responses in organisms from yeast to human to rewire metabolism, remove depolarized mitochondria, and degrade unimported precursor proteins. It remains unclear how cells maintain Δψm, which is critical for maintaining iron‐sulfur cluster (ISC) synthesis, an indispensable function of mitochondria. Here, we show that yeast oxidative phosphorylation mutants deficient in complex III, IV, V, and mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 92 publications
1
40
0
Order By: Relevance
“…Together, these results are in good agreement with earlier experiments on Δinh1Δstf1 yeast mitochondria ( Venard et al, 2003 ). Finally, in line with previous studies ( Liu et al, 2021 ), Δinh1Δstf1 strain with depleted mtDNA ( Δinh1Δstf1 rho 0 ) demonstrated an increase in the proliferation rate compared to the control rho 0 strain, although the amplitude of the effect was small ( Figure 3D ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Together, these results are in good agreement with earlier experiments on Δinh1Δstf1 yeast mitochondria ( Venard et al, 2003 ). Finally, in line with previous studies ( Liu et al, 2021 ), Δinh1Δstf1 strain with depleted mtDNA ( Δinh1Δstf1 rho 0 ) demonstrated an increase in the proliferation rate compared to the control rho 0 strain, although the amplitude of the effect was small ( Figure 3D ).…”
Section: Resultssupporting
confidence: 92%
“…Inhibition of F 1 -subcomplex ATPase activity by Inh1p decreases Δ μ˜ H + in rho 0 yeast mitochondria, whereas mitochondrial Δ μ˜ H + is essential for rho 0 cells proliferation. Indeed, increased INH1 expression decreases the growth rate of rho 0 yeast cells, while INH1 deletion accelerates growth ( Liu et al, 2021 ). Furthermore, while yeast cells with deleted i-AAA protease gene YME1 cannot survive without mtDNA, the Δyme1Δinh1 rho 0 strain proved to be viable.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, since ATP production by mitochondrial OXPHOS is impaired in many human diseases involving over 150 genes ( Liu et al, 2021 ), including Parkinson’s disease and schizophrenia ( Bergman and Ben-Shachar, 2016 ; López-Gallardo et al, 2011 ; Zhu and Wang, 2017 ), as well as during aging ( Olgun and Akman, 2007 ) and neurodegeneration ( Koopman et al, 2013 ), the results presented here suggest a mechanistic link to peroxisomal dysfunction in human mitochondrial disorders. Further explorations of this yeast model would provide important insights regarding interorganellar communication, interplay, and dynamics, while also shedding light on human disease.…”
Section: Discussionmentioning
confidence: 63%
“…In conclusion, since ATP production by mitochondrial OXPHOS is impaired in many human diseases involving over 150 genes [103], including Parkinson's disease and schizophrenia [104][105][106], as well as during aging [107] and neurodegeneration [108], the results presented here provide a clear mechanistic link to peroxisomal dysfunction in human mitochondrial disorders.…”
Section: Working Model For Interorganellar Control Of Peroxisome Dynamicsmentioning
confidence: 64%
“…Since SNF1/AMPK activation in both yeast and mammalian cells upregulates glycolysis, gluconeogenesis and mitochondrial biogenesis, while repressing ATP consumption [103,109], it makes sense that this would also enhance peroxisome proliferation because peroxisomes house several glyoxylate pathway enzymes that are necessary for gluconeogenesis [110]. Likewise, since peroxisomal metabolites (like NADH and products of the b-oxidation of very long chain FA) influence mitochondrial ATP production [111], these studies also explain how diseases affecting peroxisome biogenesis can impair mitochondria.…”
Section: Working Model For Interorganellar Control Of Peroxisome Dynamicsmentioning
confidence: 99%